Early Years with the Inuit Interpreters: Recollections and Comments from the Sidelines - Mallon, S. (Meta)

(untitled) (Les Presses de l'Université de Montréal, 1993)
AbstractThis text discusses some of the developments which occurred in the field of Inuktitut interpreting from 1974 until 1987. It outlines the problems which were encountered and describes the steps taken to correct them. Specific comments on topics such as consecutive vs. simultaneous interpretation, comprehension, problems with input and the role of the interpreter as communicator are also discussed.